Effects of different methods and times of 17-estradiol treatment on the feminization success in the narrow-clawed crayfish Astacus leptodactylus (Eschscholtz, 1823) - Harlioglu, Muzaffer M.; Yonar, Muhammet E.; Harlioglu, Ayse G.; Yonar, Serpil M.; Farhadi, Ardavan (Taylor & Francis Ltd, 2017)
Sex differentiation is a profitable technique in crayfish aquaculture. Most of the studies have focused on sex differentiation in crayfish by ablation or implantation of androgenic glands. There is no research on sex differentiation using hormones in crayfish. In the present study, the effects of 17-estradiol (E2) injections (10(-7)mol/crayfish) to females and baths (50g 17-estradiol/L) to pleopodal eggs and stage1, 2, and 3 juveniles on the feminization of freshwater crayfish, Astacus leptodactylus were investigated. Results showed that E2 injection to females, bath to pleopodal eggs and bath to stage 1, 2, and 3 juveniles increased feminization rate significantly (p<0.05) in comparison to the control in A. leptodactylus. Best feminization rate (male to female, 0.25:1) was observed after hormonal injection to the females combined with application of both for their both pleopodal eggs and stage 1, 2, and 3 juveniles. In conclusion, it is possible to obtain 75% females A. leptodactylus by E2 injection to females and bath to pleopodal eggs and stage 1, 2, and 3 juveniles. However, future studies are needed to investigate the mechanism of E2 in crayfish feminization and the sexual development of juveniles obtained from feminization.
Keywords: Reproduction; hormone injection; female crayfish; sex ratio; aquaculture